A power adjustable WPT system consisting of H-bridge and resonator - Su, Shuai (Nanyang Technological University, 2022)
This project presents the background to H-bridges and resonators in terms of the feasibility of wireless power transfer. They were also used to construct a wireless power transmission system resonance at 85kHz. The feasibility of this theoretical model is then verified with a prototype of the wireless power transmission system. The effect of the relative position of the resonator coils on the energy transfer in this prototype was also measured in this project. The power transmission of the prototype was adjusted in two ways from the point of view of adjusting the H-bridge control signal. And finally, the dissertation suggests some noteworthy ideas to improve the performance of the prototype in terms of power transfer.